Case Studies on Factors Causing Gay Behavior and Efforts to Prevent Them - Dian Rahma Yani; Frischa Meivilona Yendi (Jurnal Neo Konseling, 2021)
Nowadays gay people are no longer ashamed to show themselves to society. Many gay associations or communities have been formed and developed in Indonesia. Various attempts to introduce that gay is something common and a trend in society continue to be carried out, through mass media, both electronic and printed, which preach the legalization of gay in various countries around the world. However, this certainly cannot make people easily accept their existence, and what causes people to be gay also varies. This study aims to see what factors cause gay behavior. This type of research is qualitative research in the form of case studies. There were two subjects in this study using purposive sampling technique. The data collection instruments used in this study were interview, observation, and documentation guidelines. To describe the factors that cause gay behavior, the researcher used data analysis through three stages, namely (1) data reduction; (2) exposure data (data display); (3) drawing conclusions and verification (conclusion drawing / verifying). The data analysis technique used in this research is thematic analysis by transcribing the interviews that have been made verbatim. The results showed that there are several factors that cause gay behavior, namely first experience, the subject has experienced sexual violence in childhood and the subject has been disappointed by women. The second is from authoritarian parenting and broken home families. The three environmental factors that support the subject behave as gay. Prevention efforts that can be done are by providing sexual education methods in Islamic teachings, as well as by providing counseling services.